Exosomes rich in Wnt5 improved circadian rhythm dysfunction via enhanced PPARγ activity in the 6-hydroxydopamine model of Parkinson's disease. (1st April 2023) - Li, Zongshan; Li, Yongang; Xu, Xiaomin; Gu, Jiachen; Chen, Huimin; Gui, Yaxing
Highlights: Sleep disorder was improved in PD rat treated with BMSC derived exosomes. Striatal 5-HT and dopamine levels were increased in PD model treated with BMSC-EXO. Rescued expression of circadian rhythm associated genes in PD rat treated with BMSC derived exosomes. PPARγ expression was induced in PD rat treated with BMSC derived exosomes. BMSC derived exosomes rescued OHDA induced ΔΨm collapse in neuronal cells. Abstract: Sleep disorder is one of the most common non-motor symptoms in Parkinson's disease (PD) and even appear as early symptoms. Here we investigated the therapeutic potential of mesenchymal stem cell-derived exosomes (MSC-EXOs) on sleep disorder in PD rats. 6-hydroxydopa (6-OHDA) was used to establish the PD rat model. BMSC quiescent -EXO and BMSC induced -EXO groups were given intravenous injection 100 µg/g per day for 4 weeks, while control groups were given intravenous injection of the same volume of normal saline. The total sleep time, slow-wave sleep time and fast-wave sleep time in the BMSC quiescent -EXO and BMSC induced -EXO groups were significantly prolonged (P < 0.05) compared with PD group, while the awakening time was significantly shortened (P < 0.05). In addition, increased levels of dopamine (P < 0.05) and 5-hydroxytryptamine (P < 0.05) levels were observed in the striatum of BMSC quiescent -EXO and BMSC induced -EXO groups. Further, qPCR and western blot revealed that the mRNA levels of CLOCK, BMAL1 and PER2 in suprachiasmatic nucleus (SCN) were notably increased in BMSC quiescent -EXO and BMSC induced -EXO groups compared to those from PD rats. More importantly, peroxisome proliferation-activated receptor γ (PPARγ) activities were significantly enhanced after treatment with BMSC quiescent -EXO and BMSC induced -EXO. JC-1 fluorescence staining showed that mitochondrial membrane potential imbalance was repaired after inoculation of BMSC induced -EXO. In summary, MSC-EXOs showed the improvement of sleep disorder in PD rats through recovering circadian rhythm associated gene expression. The potential mechanisms may be related with increased PPARγ activities and rescued mitochondrial membrane potential imbalance in Parkinson striatum.